Empowering Micro, Small, and Medium Enterprises Through Product Innovation and Packaging Design: A Participatory Workshop Approach in Karya Maju Village - M Fauzul Hamdi; Ridho Mualim; Leli Syahputri; Nurmisda Ramayani; Khairani Sakdiah (Pusdikra Publishing, 2026)
This community service program aims to analyze the effectiveness of a participatory workshop model in enhancing the capacity of Micro, Small, and Medium Enterprise (MSME) actors through product innovation and packaging design. The primary challenges faced by participants included low levels of product innovation, limited production skills, and inadequate packaging quality that failed to create added value or improve market competitiveness. This study employed a descriptive approach with a participatory method involving 35 participants in Karya Maju Village. Activity stages included initial observation, conceptual training, technical demonstration, hands-on practice, intensive mentoring, and evaluation using pre-test and post-test instruments. The analysis revealed significant capacity improvements across all indicators: business opportunity awareness increased by 67%, production skills by 80%, product innovation creativity by 70%, packaging design comprehension by 80%, and entrepreneurial self-confidence by 65%. These findings indicate that an experiential learning-based participatory approach can simultaneously enhance participants’ technical and cognitive competencies. Furthermore, the integration of product innovation and packaging design has proven to contribute to product differentiation, strengthen visual identity, and improve perceived value among consumers. Accordingly, the participatory workshop model holds strategic implications as an applicable, adaptive, and sustainable approach to MSME empowerment, capable of driving improved product competitiveness grounded in local potential while broadly strengthening community economic resilience.